Measuring the Potential Involvement of Conventional Commercial Banks with Foreign Ownership in Increasing the Capital Capacity of MSMEs - Hartati Rahayu, Sri; Alif Febriyanto, Satrio; Angelina, Feymi (Fakultas Hukum, Universitas Islam Balitar, 2024)
The presence of conventional commercial banks with foreign ownership in Indonesia introduces a new dynamic in the national banking structure, with significant implications for the financing of Micro, Small, and Medium Enterprises (MSMEs). This study explores the potential involvement of these banks in enhancing the capital capacity of MSMEs, a sector traditionally dominated by the Himbara banks. Using normative legal research methods with doctrinal and comparative approaches, this study aims to identify the urgency and procedures for the involvement of conventional commercial banks with foreign ownership in MSME financing. The findings reveal that such involvement could create a mutually beneficial relationship, where MSMEs gain access to more diverse funding options, while these banks expand their customer base. These implications highlight the potential for strengthening MSME capital structures and contributing positively to the national economy.